2021
DOI: 10.1016/j.amsu.2021.102401
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous cephalosporin versus non-cephalosporin-based prophylaxis to prevent surgical site infections in colorectal surgery patients: A systematic review and meta-analysis

Abstract: Background Surgical site infection (SSI) is common in colorectal surgery patients and associated with morbidity and mortality. Guidelines recommend preoperative intravenous antimicrobial prophylaxis with aerobic and anaerobic coverage to reduce SSI risk. Cephalosporin based prophylaxis (CBP) regimens are recommended as first-line prophylaxis, and non-cephalosporin based are recommended as alternative prophylaxis (AP). We evaluate the efficacy of CBP versus AP in preventing surgical site infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The adoption of enhanced recovery after surgery (ERAS ® ) core items has been shown to decrease serious postoperative complications (POCs) and reduce postoperative hospital length of stay (LOS), readmission rates, and overall hospital costs [1][2][3][4][5][6][7][8][9]. Protocolized prophylaxis of common POCs with pharmacotherapy, such as surgical site infection (SSI) with appropriate antibiotics [10][11][12][13], venous thromboembolism (VTE) with anticoagulants [14][15][16][17], and postoperative nausea and vomiting (PONV) using multi-modal approaches [18][19][20][21][22][23], among others, coupled with preoperative risk assessments [24][25][26][27][28][29][30][31][32][33][34], has become more prevalent in surgical practice. Still, elucidation of pharmacotherapy regimens associated with lower POCs, LOS, and readmission remains somewhat nascent [5,13,16,35,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adoption of enhanced recovery after surgery (ERAS ® ) core items has been shown to decrease serious postoperative complications (POCs) and reduce postoperative hospital length of stay (LOS), readmission rates, and overall hospital costs [1][2][3][4][5][6][7][8][9]. Protocolized prophylaxis of common POCs with pharmacotherapy, such as surgical site infection (SSI) with appropriate antibiotics [10][11][12][13], venous thromboembolism (VTE) with anticoagulants [14][15][16][17], and postoperative nausea and vomiting (PONV) using multi-modal approaches [18][19][20][21][22][23], among others, coupled with preoperative risk assessments [24][25][26][27][28][29][30][31][32][33][34], has become more prevalent in surgical practice. Still, elucidation of pharmacotherapy regimens associated with lower POCs, LOS, and readmission remains somewhat nascent [5,13,16,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Protocolized prophylaxis of common POCs with pharmacotherapy, such as surgical site infection (SSI) with appropriate antibiotics [10][11][12][13], venous thromboembolism (VTE) with anticoagulants [14][15][16][17], and postoperative nausea and vomiting (PONV) using multi-modal approaches [18][19][20][21][22][23], among others, coupled with preoperative risk assessments [24][25][26][27][28][29][30][31][32][33][34], has become more prevalent in surgical practice. Still, elucidation of pharmacotherapy regimens associated with lower POCs, LOS, and readmission remains somewhat nascent [5,13,16,35,36]. Moreover, estimates of the impact of pharmacotherapy prophylaxis on the attainment of positive patient outcomes in hospitals with "homegrown" enhanced recovery audit and feedback systems are publicly non-existent unless reported on public-facing hospital webpages, which, according to some reports, may be misleading information [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies of adults undergoing colorectal surgery suggest the possibility of effectiveness of perioperative prophlyaxis for SSI prevention being related to the type of regimen being used [ 10 , 11 ], but a recent systematic review and meta-analysis concluded that there was no difference in SSI between patients receiving cephalosporin and non-cephalosporin based regimens [ 12 ]. A range of regimens is recommended in continental Europe, with the use of a Penicillin antibiotic and a Beta-lactamase inhibitor preferred in France compared with a first or second generation cephalosporin plus metronidazole or an aminoglycoside in combination with clindamycin or metronidazole in Italy and the Netherlands [ 13 – 15 ].…”
Section: Introductionmentioning
confidence: 99%